Experiences of educated youth exposed to domestic violence: Social impact to their lives - Siti Mas'udah; Lutfi Apreliana Megasari; Evan Doran (Masyarakat, Kebudayaan dan Politik, 2022)
The number of cases of domestic violence against women and children in Indonesia has escalated year by year. Various studies have revealed the impact of family violence on children, but few have sought to investigate the sociological lives of youth who have been exposed to domestic violence since childhood. This study aimed to reveal the experiences of educated youth who are exposed to domestic violence and its impact on them. This study used a qualitative method. The research informants were educated youth who had been victims of domestic violence and were currently students in the university. The results showed that children who were victims of exposure to violence had bad experiences throughout their lives. They recorded domestic violence from childhood to growing up. They believe that parents and families are parties that are unable to provide protection. In addition, exposure to violence also causes mental health disorders, poor psychological conditions, and thoughts of refusing to marry. This study concludes that exposure to domestic violence has a serious impact on children’s social development because from childhood to adulthood they grow up in a violence zone.